2010
DOI: 10.1002/humu.21334
|View full text |Cite
|
Sign up to set email alerts
|

Mutation spectrum of EYS in Spanish patients with autosomal recessive retinitis pigmentosa

Abstract: Retinitis pigmentosa (RP) is a heterogeneous group of inherited retinal dystrophies characterised ultimately by the loss of photoreceptor cells. We have recently identified a new gene (EYS) encoding an ortholog of Drosophila spacemaker (spam) as a commonly mutated gene in autosomal recessive RP. In the present study, we report the identification of 73 sequence variations in EYS, of which 28 are novel. Of these, 42.9% (12/28) are very likely pathogenic, 17.9% (5/28) are possibly pathogenic, whereas 39.3% (11/28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
80
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(87 citation statements)
references
References 34 publications
2
80
1
Order By: Relevance
“…Our previous study on 100 Japanese arRP patients indicated very likely pathogenic mutations and possible pathogenic mutations in 18% (18/100) and 8% (8/100), respectively, of the study population; these values are higher than those previously reported. [4][5][6][7] Our previous study has shown that 16% of Japanese patients with arRP displayed either the c.4957_4958insA or the c.8868C4A mutation, which accounted for 57% (15 þ 5/35) of the mutated alleles and seem to be frequent among Japanese patients with arRP. 8 However, a detailed haplotype analysis of the EYS gene has not been performed, and therefore, currently, we cannot verify whether each mutation occurred in an ancient common ancestor.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our previous study on 100 Japanese arRP patients indicated very likely pathogenic mutations and possible pathogenic mutations in 18% (18/100) and 8% (8/100), respectively, of the study population; these values are higher than those previously reported. [4][5][6][7] Our previous study has shown that 16% of Japanese patients with arRP displayed either the c.4957_4958insA or the c.8868C4A mutation, which accounted for 57% (15 þ 5/35) of the mutated alleles and seem to be frequent among Japanese patients with arRP. 8 However, a detailed haplotype analysis of the EYS gene has not been performed, and therefore, currently, we cannot verify whether each mutation occurred in an ancient common ancestor.…”
Section: Discussionmentioning
confidence: 98%
“…2,3 EYS gene mutations, which include primarily truncating and some missense mutations, have been detected in arRP-affected families of different ancestral origin and are reported to account for 5-16% of arRP cases. [4][5][6][7] Recently, we screened all EYS gene exons in 100 unrelated Japanese RP patients and, found EYS gene mutations in at least 20% of the arRP patients (see the Supplementary Table in the Supplementary Material -available online). 8 In the current study, we examined the clinical features of ten unrelated Japanese patients with RP caused by the EYS gene mutation and compared the phenotype of four patients with the homozygous c.4957_4958insA (p.S1653KfsX2) mutation, which is a major causative mutation of RP in Japan, to that of the other RP patients.…”
Section: Introductionmentioning
confidence: 99%
“…4 EYS is an important and common cause of RP in the Japanese, Spanish, British, Chinese, Israelis, and Palestinians. [5][6][7][8][9] Furthermore, a report has described that EYS-associated RP patients share a relatively uniform phenotype with near-normal central visual function up to their 20s. 10 We have previously reported that severity of RP patients with EYS mutations was relatively moderate among RP patients with various mutations.…”
Section: Introductionmentioning
confidence: 99%
“…So far, 32 genes have been implicated in arRP and 3 additional loci have been mapped (http://www.sph.uth.tmc.edu/Retnet). Most of the identified genes accounted for only 1-2% of cases each, besides EYS (MIM# 612424) and USH2A (MIM# 608400), which were found to account for up to 15.9% and up to 23%-of isolated arRP respectively (Abd El-Aziz et al 2008;Audo et al;Bandah-Rozenfeld et al;Barragan et al;Littink et al 2010) and (Rivolta et al 2000;Bernal et al 2003;McGee et al 2010).…”
Section: Introductionmentioning
confidence: 99%